Norma de gênero e instituição escolar: um estudo psicossocial sobre as estratégias de enfrentamento à homofobia nas escolas das redes públicas de ensino da região metropolitana de Belo Horizonte - Leonardo Tolentino Lima Rocha (2012)
This research focuses on the initiatives undertaken to confront homophobia by educators working within public schools of the Belo Horizonte metropolitan area. Such initiatives, designed as Intervention Projects (IP), were established as part of the final coursework for the continuing education course Project Education without Homophobia. The course was coordinated by the Center for Lesbian, Gay, Bisexual and Transgender Human Rights and Citizenship (Nuh/UFMG), and partnered with the municipal secretaries of education and the LGBT social movement. The research is dedicated to investigate: a) the theoretical and methodological articulations which gravitates around the comprehensions of homophobia, and the resources for establishing and developing the IP; b) both intra-personal and institutional negotiations that were undertaken in order to enable the implementation of the interventions. As a part of the process, 58 IPs were analyzed and five educators were selected to participate in semi-structured interviews. The analysis of theoretical and methodological linkages led to five categories, which in various ways, shows how an understanding of homophobia relates to other social phenomena such as prejudice, discrimination and sexual hierarchies. It can be seen in these articulations, that the intervention strategies emphasize the reorganization of the sexual hierarchy, from the revalorization and fixed identities and the inclusion of LGBT, rather than the declassification of gender norm and sexual hierarchies. Concerning the negotiations, it can be observed that they revolve around: personal aspects, relating to the awareness of educators to confront homophobia, and institutional aspects, which require elements of legitimacy to justify the implementation of IP in schools. Contributions from Judith Butler, Daniel Borrillo and Jacques Rancière are used to establish a theoretical framework addressing concepts of gender norms, homophobia and politics, respectively. It can be concluded that the bargain elements beheld by the educators, to deal with institutional homophobia requirements, are fragile, precarious and do not support the individual initiatives effectively what endangers the claim of existence of homophobia confrontation public policies in the education.